Trade Unions and the Industry Council Plan - Justin, Brother (Relations industrielles / Industrial Relations, 1953)
SummaryIndustry Council Systems are slowly but surely progressing in the United States. The author analyzes some of the reasons which explain what is holding them back and proposes some concrete methods of a nature to contribute to the realization of this economic-social reform which, nevertheless, is an integral part of the Church's social teachings.